Informing decisions in agent-based models — A mobile update. (July 2017) - Bell, Andrew Reid
Abstract: A range of tools exists for collecting data to inform decision processes in agent-based models (ABMs), each appropriate to modeling processes at particular scales and each with particular strengths and limitations. The issue of which tools are appropriate to which goals has been discussed in the literature at several points over the last decade, but has not been updated to reflect the way in which the cost of stakeholder engagement will shift in the near future as smartphones and mobile technologies penetrate rural areas across the world along the same path as mobile phones before them. I present the challenge of validating ABMs as closing a series of 'gaps' that characterize the separation between a real-world decision and its modeled counterpart, and illustrate the potential for mobile phones and other information and communication technologies (ICTs) to transform the modes with which ABMs are empirically informed. Highlights: I use a series of gaps to attribute the difference between real and modeled decisions. This approach helps identify contributions that mobile and smartphones can make to agent-based modeling. Empirical toolkit for ABMs should be draw more upon mobile ICTs.